Glial fibrillary acidic protein in cerebrospinal fluid of patients with spinal muscular atrophy. Issue 9 (11th August 2022) - Freigang, Maren; Steinacker, Petra; Wurster, Claudia D.; Schreiber‐Katz, Olivia; Osmanovic, Alma; Petri, Susanne; Koch, Jan C.; Rostásy, Kevin; Huss, André; Tumani, Hayrettin; Winter, Benedikt; Falkenburger, Björn; et al.
Abstract: Objective: Activated astroglia is involved in the pathophysiology of neurodegenerative diseases and has also been described in animal models of spinal muscular atrophy (SMA). Given the urgent need of biomarkers for treatment monitoring of new RNA‐modifying and gene replacement therapies in SMA, we examined glial fibrillary acidic protein concentrations in cerebrospinal fluid (cGFAP) as a marker of astrogliosis in SMA. Methods: 58 adult patients and 21 children with genetically confirmed 5q‐associated SMA from four German motor neuron disease specialist care centers and 30 age‐ and sex‐matched controls were prospectively included in this study. cGFAP was measured and correlated to motor performance and disease severity. Additionally, we compared cGFAP with neurofilament light chain concentrations in cerebrospinal fluid (cNfL). Results: cGFAP concentrations did not differ from controls but showed higher levels in more severely affected patients after adjustment for patients' age. Normalized cNfL values were associated with disease severity. Within 14 months of nusinersen treatment, cGFAP concentrations did not change, while cNfL decreased significantly. Interpretation: cGFAP is not an outstanding biomarker in SMA, but might support the hypothesis that glial activation is involved in SMA pathology. Unlike previously suggested, cNfL may be a promising biomarker also in adult patients with SMA, which should be subject to further investigations.